Developing safety aptitude measurement tool for contract workers during turnaround operation in petrochemical plants in Gebeng - Abdul Wahab, Muhammad Nubli; Kassim, Hafizoah; Abdul Aziz, Nawawi (2007)
Turnaround is the most significant inspection and maintenance event which takes place in the lifecycle of production unit at a plant. In conducting inspection, more than 70% of the expenditure is incurred during a turnaround. During this period, it involves peak contract staffing around 3000 to 5000 per session. Contract workers are needed because employing qualified competent workers for peak operation is more effective compared to employing permanent staff. Thus, contract workers' performance is one of the key success factors of the turnaround operation. However, the main problems during turnaround are contractor-related such as contractors' availability and skills are not always as good as their proposal suggests, and contractor safety performance is often not up to the clients' safety standard. Findings at one of the petrochemical plants in Gebeng show that the safety standard of contractors during turnaround is only 40% of the normal standard. Due to this, it is important to collaborate with the industries to identify problems caused by contract worker and propose solutions. This research focuses on defining safety aptitude problems among contract workers, designing a safety aptitude measurement tool, and thus, proposing a solution to the industries as well as the contractors in employing low-risk workers. Hopefully, this research will initiate direct relationship between soft skills and performance of the industries. From this research, safety aptitude measuring tool, safety aptitude domain descriptors, safety aptitude descriptors, safety aptitude matrix map have been developed. These tools have been tested with clients to understand the accuracy of the tools. This research has proven that the tools can be used to help measuring safety aptitude among workers and enhancing safety at the workplace.